The impact of employees’ experience of high-performance work systems on innovative behavior in professional service firms - Arshad, Beenish; Hassan, Hamid; Azam, Akbar (Frontiers in Psychology, 2024)
This research examines the impact of employees’ experience of high-performance work systems (HPWS) on their innovative behavior. The study draws upon social exchange theory to propose that employees’ experience of HPWS influences their innovative behavior directly and through sequential mediation of social capital development and knowledge-sharing behavior. Additionally, the study uses the Elaboration Likelihood Model to highlight that individuals’ need for cognition strengthens the relationship between employees’ knowledge-sharing and innovative behaviors. The study employed a time-lagged quantitative research design with survey data from 262 job incumbents in professional service firms. The proposed model was tested using the PLS-SEM two-stage approach. The findings of the study confirm the proposed direct and indirect relationships. Moreover, the findings also confirm that the need for cognition strengthens the relationship between knowledge-sharing and individual innovation behaviors. The study posits that employees’ experience of HRM systems can influence their innovative behavior as a reciprocal exchange toward the employer. Moreover, this study presents a comprehensive model that highlights the interplay of social and cognitive factors that can influence the relationship between HPWS and employees’ innovation behavior. This study also fills a gap in the existing literature by highlighting the antecedents of innovative behavior in professional service firms.